2022
DOI: 10.1002/jctb.7091
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic framework‐based heterojunction photocatalysts for organic pollutant degradation: design, construction, and performances

Abstract: Heterogeneous photocatalysis has been considered one of the most attractive alternative routes to transforming naturally abundant, clean, and sustainable solar energy into chemical energy. Nowadays, the most popular heterogeneous photocatalyst, titanium dioxide, has already found applications for water splitting to produce hydrogen and oxygen, for the degradation of organic pollutants, for air purification, and for the creation of self‐cleaning coatings. However, TiO2 has a significant limitation: a large band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 196 publications
0
10
0
Order By: Relevance
“…This result is consistent with the EIS result. Meanwhile, although it is difficult to judge the heterostructure of Ce-doped biochar, we carefully studied the related literature [ 41 , 42 ] and believe that the heterostructure of our catalyst can be judged by the heterostructure of cerium oxide. Previous studies in the literature have shown that, usually, the positions of band edges for CeO 2 use Mott–Schottky plots and obtain UV-Vis DRS results.…”
Section: Resultsmentioning
confidence: 99%
“…This result is consistent with the EIS result. Meanwhile, although it is difficult to judge the heterostructure of Ce-doped biochar, we carefully studied the related literature [ 41 , 42 ] and believe that the heterostructure of our catalyst can be judged by the heterostructure of cerium oxide. Previous studies in the literature have shown that, usually, the positions of band edges for CeO 2 use Mott–Schottky plots and obtain UV-Vis DRS results.…”
Section: Resultsmentioning
confidence: 99%
“…The light shielding and reversible backward reactions are suppressed in this type of configuration, resulting in higher separation of charge carriers, lower recombination rate, and improved mobility that finally contributes to efficient photocatalytic quantum yield. 30,31 Table 2 provides an overview of comparison of various types of Z-scheme photocatalysts with their properties and drawbacks.…”
Section: Classifications Of Z-scheme Heterojunctionsmentioning
confidence: 99%
“…In the last century, the approach to making solid-state structures has been largely serendipitous [13][14][15]. Metal-organic frameworks (MOF) or porous coordination polymers, which constructed from metal nodes or clusters that connected by organic ligands coordinately, have emerged as a promising class of materials with high porosity, diverse composition, tuneable pore structure [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%